HealthCare in Pakistan - Ujan, Imran Anwar; Shah, Asadullah; Bhutto, Arifa (Islamic countries society of Statistical Sciences, 2022)
Pakistan's health system has evolved over time, with roots in mediaeval medicine, conventional health care, health for population, primary health care, and health system supporting for improved health outcomes. The major goals of the health-care system are improved health, fair risk and financial distribution, and receptiveness to the population's non-medical demands. Declining health-care spending, an updated private health-care sector, and a thriving pharmaceutical production, the government can only decrease calamitous health-care costs for the poor and underprivileged by ensuring that the public health system is efficient, effective, accessible, and responsive. Inter-sectoral association, community contribution, social fortification, equitable resource delivery, people-centered health policy, health workforce advancement, evidence-based health information system, and essential medicine quality confidence will all help to strengthen Pakistan's health system